The Ancient Kitchen Space in the Light of Medical and Gastronomic Literature - Rzeźnicka, Zofia (In the Kitchen. Cultural Sketches on Space, 2019)
The aim of the present article is to reconstruct the ancient kitchen space according to the recipes given in the Latin cookbook known as De re coquinaria (4th century A.D.), the agricultural work De agricultura by Cato the Elder (3rd/2nd century B.C.) and Greek medical treatises by Galen (2nd/3rd century A.D.) and Oribasius (4th century A.D.). On their basis the author describes the most important kitchen utensils and the way they were used. Moreover, she characterises the most common thermal treatments utilized in culinary art of that time.